Back Cover: Enantioselective Oxidative Rearrangements with Chiral Hypervalent Iodine Reagents (Chem. Eur. J. 12/2016). Issue 12 (17th February 2016) - Brown, Michael; Kumar, Ravi; Rehbein, Julia; Wirth, Thomas
Abstract : Hypervalent iodine reagents offer an environmentally benign alternative to heavy‐metal catalysts for stereoselective reactions. By using these powerful reagents, simple and readily accessible molecules, such as 1, 1‐disubstituted alkenes (represented by the red/yellow/green blocks on the left), can be efficiently rearranged to enantioenriched α‐aryl ketones (on the right). The background blue lights represent the pool of organic molecules/atoms from which the simple molecules are formed and the scientist's hand is approaching the starting material to promote the reaction. More information can be found in the Full Paper by T. Wirth et al. onpage 4030 ff.